Directed technical change, the elasticity of substitution and wage inequality in developing countries. - Behar, A (Department of Economics (University of Oxford), 2009)
We develop a model of endogenous skill-biased technical change in developing countries. The model reconciles wildly dispersed existing estimates of the elasticity of substitution between more and less educated workers. It also produces an estimating equation for the elasticity, which allow us to produce overdue estimates for developing countries. With four types of data, elasticity estimates for developing countries are consistently about 2. In a skill-biased technical change framework, this estimate makes sense of what appears to be little or no correlation between relative skill supply and wage inequality.